Faunistic inventory and zoogeographical analysis of the ground beetles (Coleoptera, Carabidae) of Garf Raydah Nature Reserve, Southwestern of Saudi Arabia, and description of a new species of Paussinae - Abdel-Dayem, Mahmoud S.; Rasool, Iftekhar; Elgharbawy, Ali A.; Nagel, Peter; Aldhafer, Hathal M. (Zootaxa, 2018)
Study of ground beetles of the Garf Raydah Nature Reserve, located in the Asir Mountains of southwestern Kingdom of Saudi Arabia (KSA) resulted in one species, Paussus abditus Nagel, sp. n. described as new to science. Thirteen species (21.3%) are reported as new country records and fifteen species (24.6%) are new records for Asir Province. Adult beetles were collected from 2013 to 2017. The determination of this material yielded a total of 61 species in 40 genera and 17 tribes belonging to nine subfamilies of Carabidae. The species richness represented approximately 36.1% of carabid species previously reported from KSA. The most species rich tribes were the Lebiini (20 species), the Harpalini (10 species), and the Bembidiini (6 species). The life form analysis of adults indicated 18 life form types that are grouped into three categories, Zoophagous (77.1%), Mixophytophagous (18.0%), and Myrmecophilous (4.9%). Zoogeographical analyses indicated that the Afrotropical (19.3%) and the Saharo-Arabian (19.3%) species dominate the carabid fauna of this region of KSA. Coryza cf. maculata (Nietner, 1856) is considered the only Oriental representative. Only one cosmopolitan species, Perigona nigriceps (Dejean, 1831), was collected. Eleven endemics were identified; six species are considered KSA endemics and five are Arabian Peninsula endemics.